2008
DOI: 10.1002/cne.21766
|View full text |Cite
|
Sign up to set email alerts
|

Differential reaction of outgrowing olfactory neurites monitored in explant culture

Abstract: Olfactory sensory neurons (OSNs) send their axons to distinct glomeruli in the olfactory bulb. On the way to their target, outgrowing axons are guided, fasciculated, and resorted before they extend in homotypic bundles to the glomerulus. The molecular mechanisms underlying these complex processes supposedly involve multiple intrinsic and extrinsic cues. Although the contribution of typical guidance molecules has been proposed, a detailed understanding of the olfactory wiring process remains elusive. By using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…1E,F). The mOR256-17-GFP olfactory sensory neurons traversed the cribriform plate and coalesced into glomeruli as previously described1727 but the number of olfactory sensory neurons was strongly reduced in MT1-MMP −/− compared to controls (inserts in Fig. 1E–G).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…1E,F). The mOR256-17-GFP olfactory sensory neurons traversed the cribriform plate and coalesced into glomeruli as previously described1727 but the number of olfactory sensory neurons was strongly reduced in MT1-MMP −/− compared to controls (inserts in Fig. 1E–G).…”
Section: Resultssupporting
confidence: 75%
“…In order to investigate if MT1-MMP also impacts on the formation of osseous structures which allow neuronal trajectories to access the brain we traced distinct olfactory sensory neurons from the nasal cavity into the olfactory bulb using mOR256-17-GFP mice17 crossbred with MT1-MMP −/− or wild-type controls (n = 4; Fig. 1E,F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the use of these mice may not be suitable for many studies. The OMP-GFP mice have previously been used for explant assays to analyse olfactory axon growth and provided good resolution of axons using a single time point (Luxenhofer et al, 2008). However, we found that the GFP expression in living axons was weak and faded rapidly with repeated exposure and hence we were unable to obtain high magnification, high resolution images of OMP-GFP axons using timelapse microscopy.…”
Section: Discussionmentioning
confidence: 75%
“…For this study, adult wildtype C57BL/6J mice purchased from Charles River (Sulzfeld, Germany) and animals from our previously generated transgenic mouse line which carry a targeted mutation of IRES-tauGFP at the mOR256-17-locus [11] were used. All animals were kept at a 12h/12h light/dark cycle and had free access to water.…”
Section: Methodsmentioning
confidence: 99%